Cranial anatomical structures with high sexual dimorphism in metric and morphological evaluation: A systematic review - da Silva, Juliana Calistro; Strazzi-Sahyon, Henrico Badaoui; Nunes, Gabriel Pereira [UNESP]; Andreo, Jesus Carlos; Spin, Maurício Donalonso; Shinohara, André Luís (Elsevier, 2023)
The mastoid process has attracted the attention of several researchers due to its protected position at the base of the skull and the fact that it is relatively compact, in addition to being highly resistant and dimorphic, considered as a gold standard anatomical structure in the determination of the sexual dimorphism of skulls. However, intrinsic and extrinsic factors may influence this anatomical structure over time, providing contradictory and ambiguous data. Therefore, other anatomical structures need to be evaluated concurrently with the mastoid process to provide better accuracy and reliability of skull sexual dimorphism data. Thus, the objective of this systematic review was to evaluate the degree of reliability of the mastoid process to determine sexual dimorphism compared to other dimorphic structures, since there are still no systematic reviews on the subject in the literature. This review follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and was recorded in the Prospective International Systematic Reviews Registry (PROSPERO) (CRD 42023395167 Systematic Registry) (CRD420223). The inclusion criteria for selecting the studies were based on the PICO question: “Are skull anatomical structures reliable as alternatives to determine sexual dimorphism compared to the mastoid process?“. A literature search for studies was performed in the MEDLINE Scopus, Web of Science, LILACS, and Cochrane Library databases. The Kappa agreement presented an approval level of (k = 0.93). This systematic review analyzed 13 ex-vivo studies published between 2008 and 2023. The risk of bias was considered low in 12 of the studies, and high in 1 study. Based on the findings, it can be concluded that even with the limitations of this systematic review, quantitative and qualitative analyses are essential in sexual identification of human skulls, and different anatomical structures can be used as references in addition to the mastoid process, with high reliability and precision, among them the; glabella, frontal profile, superciliary arch, bizygomatic width, maximum cranial length, and nasal height.
Keywords: Forensic anthropology; Human identification; Mastoid; Sex characteristics